Neuroprotective and inflammatory biomarkers in pediatric drug-resistant epilepsy: Interplay between GDNF, IL-1β and vitamin D 25-OH - Saing, Johannes H.; Sari, Dina K.; Supriatmo, Supriatmo; Fithrie, Aida; Rusda, Muhammad; Amin, Mustafa M.; Pratama, Muhammad A. (Narra J, 2024)
Drug-resistant epilepsy in pediatric patients is associated with neuroinflammation and neurodegeneration. Vitamin D 25-OH exerts neuroprotective effects, while glial cell line-derived neurotrophic factor (GDNF) and the proinflammatory cytokine interleukin-1β (IL-1β) are implicated in the mechanisms of neuroinflammation and epileptogenesis. The aim of this study was to investigate the relationship between vitamin D 25-OH, IL-1β, and GDNF levels with seizure severity and frequency in children with drug-resistant epilepsy. A cross-sectional study was conducted at Adam Malik Hospital, Medan, Indonesia, among children with drug-resistant epilepsy. Vitamin D 25-OH, IL-1β and GDNF levels were measured using enzyme-linked immunosorbent assay (ELISA). Epilepsy severity was assessed using the Hague Seizure Severity Scale (HASS), while seizure frequency was assessed using the Global Assessment of Severity of Epilepsy (GASE). The present study identified a significant correlation between GDNF levels and epilepsy severity, as measured by the HASS score (r=0.318; p=0.006). However, no significant correlation was observed between vitamin D 25-OH or IL-1β levels and epilepsy severity or seizure frequency (p>0.05). IL-1β levels correlated significantly with GDNF levels (r=0.525; p=0.001), but IL-1β did not directly correlate with seizure frequency or epilepsy severity. In conclusion, GDNF levels significantly correlated with epilepsy severity, suggesting that GDNF may serve as a potential biomarker for assessing epilepsy severity. However, further studies investigating the role of GDNF as a potential neurotrophic factor in the pathophysiology of epilepsy and its possible application as a therapeutic target are important.